Changing the curriculum : the impact of reform on primary schooling in Hong Kong - Adamson, Bob; Kwan, Tammy; Chan, Ka-ki (Hong Kong University Press, 2000)
The Target Oriented Curriculum (TOC) is arguably the most comprehensive, fundamental and controversial attempt to promote systemic curriculum reform in Hong Kong. It aimed at a radical change in the nature of knowledge, pedagogy and assessment in schools.